Communication failures during clinical handovers lead to a poor patient outcome: Lessons from a case report. (29th April 2015) - Manias, Elizabeth; Geddes, Fiona; Watson, Bernadette; Jones, Dorothy; Della, Phillip
In the emergency department, communication failures occur in clinical handover due to the urgent, changing and unpredictable nature of care provision. We present a case report of a female patient who was assaulted, and identify how various factors interacted to produce communication failures at multiple clinical handovers, leading to a poor patient outcome. Several handovers created many communication failures at diverse time points. The bedside medical handover produced misunderstandings during verbal exchange of information between emergency department consultants and junior doctors, and there was miscommunication involving plastic registrars. There was a failure in adequately informing the general practitioner and the patient relating to follow-up care after discharge. Deficiencies of communication occurred with conveying changes in an investigative report. Communication could be improved by dividing the conduct of handover in a quiet room and at the bedside, ensuring multiple sources of information are used and encouraging role-modelling behaviours for junior clinicians.